The Effect of Using Youtube Videos on Students’ Listening Skill at SMK Abdurrab Pekanbaru - Aprilia, Elmiza; Nuardi, Nuardi (Journal of English and Arabic Language Teaching, 2024)
This research aims to test whether there is a significant difference before and after use of YouTube videos on students' listening skills at SMK Abdurrab Pekanbaru. This research use quantitative approach with a pre-experimental design, the research focuses on one group pre-test and post-test design. The population comprised 165 eleventh-grade students, with a purposive sampling technique selecting 25 students from class 11 TLM 3. Data were gathered using pre-tests and post-tests administered through Google Forms, with treatment delivered using YouTube videos over four sessions. The data were analyzed using SPSS 23, employing a Paired Sample T-test. The findings indicate a significant improvement in students' listening skills. The mean pre-test score was 42.2, while the mean post-test score increased to 79.8. The study used Paired Sample T-test as the data analysis a significance value of 0.000 (<0.05), demonstrating a statistically significant difference between pre-test and post-test scores. In conclusion, the use of YouTube videos effectively enhances students' listening skills, as evidenced by the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha).